Case Report: Penanganan Obstruksi Esofagus Pada Anjing Labrador Retrievers - Tri Utami; Tarsisius Considus Tophianong (JURNAL KAJIAN VETERINER, 2019)
Esophageal obstruction is a condition that is commonly experienced by dogs and causes disruption to the mobilization of food and water to the stomatch. The aim of this study is to provide information on the management of esophageal obstruction in a dog based on the type and location of the obstruction. The material used in this case study is a Labrador retriever dog, female, 2 years old, brownish red and weighing 24 kg. Based on history, clinical symptoms and radiographic examination, the diagnosis of this case was obstruction of a foreign body in intraluminal esophagus. Before treatment, the dog was anesthetized by premedication Atropine sulfate at 0.02 mg/kg body weight sub-cutaneously, and induction of anesthesia through combination injection of Ketamin HCL dose 10 mg/kg body weight and Xylazine dose 2 mg/ kg body weight intramuscularly. Goal treatment that has been done in this case is taking a foreign body in the form of a piece cow bone in intraluminal esophagus through the oral cavity.